Investigación educacional Evidencias para la innovación educativa - Sánchez Bravo, Alejandra (Ariadna Ediciones, 2022)
This work gives an account of the investigative work that has undertaken by teachers of schools and high schools in collaboration with male and female academics, who carry out their work in the southern part of Chile. The school-university collaborative alliance is an option to better address the challenges that education imposes.